TBLT IN CHINA (2001-2011): THE CURRENT SITUATION, PREDICAMENT AND FUTURE - Shaoqian, Luo; Baoshu, YI (Indonesian Journal of Applied Linguistics, 2013)
Abstract: With the reform of English education in China since 2001, a communicative and task-based language teaching has emerged into Chinese English classroom. To understand task-based language teaching (TBLT) practice in China, a synthesis study was conducted to analyze the current situation and predicament of TBLT in China over the last ten years based on the published TBLT articles (2001-2011) in Chinese journals and educational newspapers. The study shows that there is questioning and criticism on the effectiveness of TBLT in the forein languagae teaching classes despite the amazing growth of research in TBLT in China. It is also found that the predicament of TBLT may be attributable to a variety of factors such as no professional and systematic training TBLT for teachers, little knowledge of the latest development of TBLT, differences in student English proficiency, gap between local educational levels, no enough educational funds as well as misunderstanding and mispractice of TBLT. Thus, how to appropriately adapt and localize TBLT in China has become the major concern of researchers and educators as well as teachers. To solve the problem, this paper puts forward some suggestions to localize TBLT in the Chinese context, which is concerned with (1) task design; (2) integrating target tasks and pedagogical tasks; (3) balance between meaning and form; (4) tasks for big classes; (5) developing school based textbooks and (6) combining tasks and other teaching principles. Such a context-based approach to TBLT could provide a reference for other contexts similar to China.